Rewarming With Closed Thoracic Lavage Following 3-h CPR at 27°C Failed to Reestablish a Perfusing Rhythm - Nivfors, Joar O.; Mohyuddin, Rizwan; Schanche, Torstein; Nilsen, Jan Harald; Valkov, Sergei; Kondratiev, Timofei V.; Sieck, Gary C.; Tveita, Torkjel (Frontiers in Physiology, 2021)
Introduction: Previously, we showed that the cardiopulmonary resuscitation (CPR) for hypothermic cardiac arrest (HCA) maintained cardiac output (CO) and mean arterial pressure (MAP) to the same reduced level during normothermia (38°C) vs. hypothermia (27°C). In addition, at 27°C, the CPR for 3-h provided global O2 delivery (DO2) to support aerobic metabolism. The present study investigated if rewarming with closed thoracic lavage induces a perfusing rhythm after 3-h continuous CPR at 27°C. Materials and Methods: Eight male pigs were anesthetized, and immersion-cooled. At 27°C, HCA was electrically induced, CPR was started and continued for a 3-h period. Thereafter, the animals were rewarmed by combining closed thoracic lavage and continued CPR. Organ blood flow was measured using microspheres. Results: After cooling with spontaneous circulation to 27°C, MAP and CO were initially reduced by 37 and 58% from baseline, respectively. By 15 min after the onset of CPR, MAP, and CO were further reduced by 58 and 77% from baseline, respectively, which remained unchanged throughout the rest of the 3-h period of CPR. During CPR at 27°C, DO2 and O2 extraction rate (VO2) fell to critically low levels, but the simultaneous small increase in lactate and a modest reduction in pH, indicated the presence of maintained aerobic metabolism. During rewarming with closed thoracic lavage, all animals displayed ventricular fibrillation, but only one animal could be electro-converted to restore a short-lived perfusing rhythm. Rewarming ended in circulatory collapse in all the animals at 38°C. Conclusion: The CPR for 3-h at 27°C managed to sustain lower levels of CO and MAP sufficient to support global DO2. Rewarming accidental hypothermia patients following prolonged CPR for HCA with closed thoracic lavage is not an alternative to rewarming by extra-corporeal life support as these patients are often in need of massive cardio-pulmonary support during as well as after rewarming.